Authentic leadership, perceived insider status, error management climate, and employee resilience: A cross-level study - Li, Xu; Zhang, Jianyu (Frontiers in Psychology, 2022)
Employee resilience is of great significance for organizations to resist pressures, overcome crises and achieve sustainable development. However, existing research has largely failed to explore its situational triggers. Drawing on social information processing theory, a cross-level study was conducted to theorize the underlying mechanisms through which authentic leadership facilitates employee resilience. Based on a two-wave time lagged design, the data were obtained from 85 team leaders and 417 employees in China. The results of the cross-level model showed that authentic leadership was positively related to employee resilience. Perceived insider status and error management climate both played a partial mediating role linking authentic leadership and employee resilience. Error management climate positively moderated the relationship between perceived insider status and employee resilience. This paper not only contributes to revealing the cross-level effect of authentic leadership on employee resilience, but also provides some managerial practices.